Micro‐stromatolitic laminations and the origins of engraved, oxalate‐rich accretions from Australian rock art shelters. Issue 6 (7th September 2021) - Green, Helen; Gleadow, Andrew; Finch, Damien; Myers, Cecilia; McGovern, Jenna
Abstract: Distinctive, dark‐coloured, glaze‐like mineral accretions are common on low‐angle surfaces in sandstone rock shelters in the Kimberley region of north‐western Australia, where they provide an attractive medium for the production of deep engravings, and occasionally, are associated with painted rock art. These accretions form within the shelter dripline and are similar to those reported from other sites around the world, where they have been used for radiocarbon dating of associated rock art. This study uses extensive field observations and mineralogical analysis of 77 such oxalate‐rich accretions collected at 41 different sites across a wide area of the north Kimberley region. The mineralogy of these accretions is dominated by well‐crystallised calcium oxalate and sulphate minerals, most commonly whewellite and gypsum, with significant occurrences of phosphates in some samples. The accretions are typically several millimetres thick and characterised by distinctive internal laminations that show regular stacked undulations, giving a stromatolitic appearance under the microscope. Together with other apparently microbial features observed under the scanning electron microscope, these features provide strong support for a microbiological origin for these oxalate‐rich accretions. The well‐crystallised nature of the oxalates and the preservation of fine laminar features within the accretions supports their use for radiocarbon dating.